Explaining primary science - Chambers, Paul; Souter, Nicholas (SAGE, 2017)
Successful science teaching in primary schools requires a careful understanding of key scientific knowledge. Explaining Primary Science covers all the major areas of science relevant for beginning primary school teachers, explaining key concepts from the ground up, helping trainees develop into confident science educators.